Higher flight activity in the offspring of migrants compared to residents in a migratory insect - Dällenbach, L.; Glauser, A.; Lim, K.; Chapman, J.; Menz, Myles (The Royal Society Publishing, 2018)
Migration has evolved among many animal taxa and migratory species are found across all major lineages. Insects are the most abundant and diverse terrestrial migrants, with trillions of animals migrating annually. Partial migration, where populations consist of resident and migratory individuals, is ubiquitous among many taxa. However, the underlying mechanisms are relatively poorly understood and may be driven by physiological, behavioural or genetic variation within populations. We investigated the differences in migratory tendency between migratory and resident phenotypes of the hoverfly, Episyrphus balteatus, using tethered flight mills. Further, to test whether migratory flight behaviour is heritable and to disentangle the effects of environment during development, we compared the flight behaviour of laboratory-reared offspring of migrating, overwintering and summer animals. Offspring of migrants initiated more flights than those of resident individuals. Interestingly, there were no differences among wild-caught phenotypes with regard to number of flights or total flight duration. Low activity in field-collected migrants might be explained by an energy-conserving state that migrants enter into when under laboratory conditions, or a lack of suitable environmental cues for triggering migration. Our results strongly suggest that flight behaviour is heritable and that genetic factors influence migratory tendency in E. balteatus. These findings support the growing evidence that genetic factors play a role in partial migration and warrant careful further investigation.